QUALIMETRIC PARAMETERS OF QUALITY ASSESSMENT IN EDUCATION - Baybaeva Muxayyo Xudaybergenovna; Karimova Maxbuba Muqimjonovna (Scholar Express Journal, 2021)
At present, quality assurance of educational services is the main task of educational institutions. A variety of methods are used to assess the quality of education and efforts are made to improve it. This article provides information on the qualitative parameters of qualitative assessment of education and the science of qualimetry
Keywords: Educational Process; Quality Of Education; Qualimetric Parameters; Technologies